ISLAM AS THE STATE IDEOLOGY OF THE GOLDEN HORDE: STAGES OF FORMATION AND THE ROLE OF SUFI ORDERS - Zharas Akhan, Tuba Tombuloğlu (Вестник ЗКУ, 2026)
This article provides a comprehensive analysis of the institutionalization of Islam within the state and social structures of the Ulus of Jochi (the Golden Horde). The study examines the political aspects of religious transformation from the reign of Batu Khan to Uzbeg Khan. The central focus of the paper is to identify the factors that facilitated the penetration of Islam into nomadic society. The author highlights the unique role of Sufi orders (Yassawiya, Kubrawiya, Naqshbandiya) in disseminating Islamic teachings across the Golden Horde. Furthermore, the article analyzes the instrumentalization of Islam as a tool for state centralization and its significance in foreign policy, particularly regarding the alliance with the Mamluk Sultanate. The study concludes by describing the decisive role of Islam within the bureaucratic system of the Golden Horde.